Effect of the Antibiotic Neomycin on the Toxicity of the Glycoside Vicine in Rats - Mahmoud S. Arbid; Khaled M. M. Koriem; Gihan F. Asaad; Hoda A. Megahed (Journal of Toxicology)
Vicine is hydrolyzed by microflora to highly reactive free radical generating compound divicine which causes mortality and other adverse effects. This study in the rats established the effect of a broad spectrum and poorly absorbed antibiotic, neomycin sulfate on the toxicity of vicine. The results showed extremely decrease in mortality rate in the group pretreated with neomycin. Hemoglobin (Hb) concentration, hematocrit (Hct) value, and red blood cells (RBCs) count were significantly decreased after injection of vicine and the improvement of these values in the group pretreated with neomycin. The same results were observed in white blood cells (WBCs). The results showed a significant decrease in glucose level and returned to normal in group pretreated with neomycin. Glutathione (GSH) was significantly decreased in the vicine group and returned to normal value in the group pretreated with neomycin. Lipid peroxide (TBARs) was significantly increased in the group treated with vicine and neomycin pretreated group decreased to the normal level. Glucose-6-phosphate dehydrogenase (G6-PD) activity was significantly decreased and returned to normal level in rats pretreated with neomycin. Serum protein and globulin were significantly decreased but serum albumin showed insignificant decrease in vicine and neomycin groups compared to control. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were significantly decreased in the vicine group. The group pretreated with neomycin showed significantly increased activities of AST and ALT compared with vicine group. In conclusion, neomycin pretreatment of rats injected with glycoside vicine decreased to a great extent of its toxic and mortality effects and is useful in favism and hemolytic anemia.